2001
DOI: 10.14198/ingeo2001.26.07
|View full text |Cite
|
Sign up to set email alerts
|

El índice NAO y la precipitación mensual en la España peninsular

Abstract: En el artículo se realiza un análisis detallado a resolución mensual de la correlación existente entre un índice NAO y la precipitación en la España peninsular. El índice NAO se ha construido a partir de la presión atmosférica en superficie en Lisboa y Reykjavik, mientras que las series de precipitación mensual utilizadas corresponden a 41 observatorios durante el período 1900-1994. Los resultados obtenidos permiten distinguir cuatro grupos de meses: de octubre a marzo, inclusives, con buena correlación negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 7 publications
5
37
0
4
Order By: Relevance
“…Rodríguez-Puebla et al (1998) showed a significant correlation between annual precipitation in the central/western region and the December NAO index. Also, Martín-Vide & Fernández (2001) indicated a spatial gradient of the NAO influence on precipitation from the southeast of the Iberian Peninsula (strong) to the north and east (weak). These authors also showed important monthly differences in the NAO influence.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Puebla et al (1998) showed a significant correlation between annual precipitation in the central/western region and the December NAO index. Also, Martín-Vide & Fernández (2001) indicated a spatial gradient of the NAO influence on precipitation from the southeast of the Iberian Peninsula (strong) to the north and east (weak). These authors also showed important monthly differences in the NAO influence.…”
Section: Discussionmentioning
confidence: 99%
“…The NAO affects winter precipitation significantly in the Iberian Peninsula (Trigo et al, 2004;Ullbrich et al, 1999;Martín-Vide and Fernández, 2001). Nevertheless, other atmospheric circulation patterns can be identified during the boreal winter in Western Europe (Barnston and Livezey, 1987).…”
Section: General Atmospheric Circulation Patternsmentioning
confidence: 99%
“…Several papers have indicated that interannual precipitation variability and drought occurrence in Spain are related to changes in the main atmospheric circulation modes on global and hemispheric spatial scales (von Storch et al, 1993;Rodríguez-Puebla et al, 1998;Rodó et al, 1997;Pozo-Vázquez et al, 2001Martín-Vide and Fernández, 2001). Other papers have analysed the influence of weather types on precipitation (Trigo and DaCamara, 2000;Goodess and Palutikof, 1998;Martín-Vide, 2002;Goodess and Jones, 2002;Corte-Real et al, 1998;Esteban et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Northern Atlantic Oscillation (NAO) refers to the atmospheric mass distribution between the Arctic and the subtropical Atlantic and has a strong impact on the European climate, including that of the Iberian Peninsula (where low NAO leads to a humid growing season; Martín-Vide & Fernández-Belmonte, 2001), as well as that of the eastern coast of North America. NAO can be assessed through an index based on the pressure differences between a northern location (usually Iceland) and more southern locations (usually the Azores Islands or the Portuguese coast).…”
Section: Introductionmentioning
confidence: 99%